An Overview of the Performance of Public Infrastructure Megaprojects in Kenya - Austin Baraza Omonyo (European Scientific Journal, ESJ, 2017)
The need for this study arose from the thesis that infrastructure megaprojects are often delivered over budget, behind schedule, with benefit shortfalls, over and over again. Many studies have been conducted towards this conclusion but these studies have not included Kenya which is increasingly adopting megaprojects as a model for delivering public goods and services. Through this quantitative study utilizing a cross-sectional census survey design, the performance of 27 completed public infrastructure megaprojects was assessed using broader measures of project success. The findings agree that these projects are delivered over budget and behind schedule but not with benefit shortfalls. It is also confirmed that process or project management success does not necessarily lead to product or organizational success. It is recommended that public infrastructure megaproject sponsors and implementers adopt project structures that allow for innovation through the use of advanced technology. Such structures should encourage the use of competitive tendering and a preference for pain/gain contractual arrangements to accommodate the differences in risk preferences between the client and the contractor, and to minimize the incidences of agency problem among the various stakeholders.